A Comparative study on the audit quality attributes and perception of the audit partners and financial statement users - Arya Jain; Masih, Aatish; John, Jessy (AU Hybrid International Conference 2024 on " Entrepreneurship & Sustainability in the Digital Era" under the theme of "People Centric Knowledge in Intelligence World", 2023)
Purpose: One of the most important topics in accounting literature is the quality of information presented in financial statements. The audit helps in maintaining the records and verification of the books of accounts. The audit fosters trust among all the parties involved including banks, debenture holders, creditors and other stakeholders. Therefore, in order to secure the stakeholders related to any organization audit is undertaken. The financial auditors report provides users with the confirmation that the company will continue to operate in the foreseeable future and the activity reported in the financial statement is sustainable, at least in the medium term. In this regard the literature has grown significantly in the terms of analyzing the quality of financial audit this provides the purpose for undertaking this research. Research design, data and methodology: This research is exploratory research that is it is quantitative in nature and investigates the research question that has not previously been studied in depth. The methodology adopted for collecting responses with respect to the research is judgmental sampling which covered employees associated with financial sector. The data is collected from 62 individuals working in financial sector so as to measure their knowledge about financial audit and also to know the attributes and perceptions that influences the audit quality. Results: The result outlines the major attributes and perception effecting the audit quality, it was found out by performing factor analysis, and analyzing the data collected. Conclusions: There have been researches on the audit quality but this one contributes in identifying the majorly affecting characteristics of auditors on audit quality and perceptions.